2022
DOI: 10.3389/fmed.2022.895923
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni-Associated Hemophagocytic Lymphohistiocytosis and Guillain-Barre Syndrome: A Case Report

Abstract: Campylobacter jejuni (C. jejuni), a Gram-negative bacterium, belongs to microaerobic bacteria. We reported a 21-year-old male patient diagnosed with hemophagocytic lymphohistiocytosis (HLH) due to C. jejuni infection, who presented with multiple clinical manifestations of peripheral nerve injury, such as ophthalmoplegia, facial paralysis, and urinary retention during the treatment. Electromyography showed neurogenic injury and the final diagnosis was Guillain-Barre Syndrome (GBS). After treatment of dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…HLH can present with a range of clinical and laboratory features, including fever, splenomegaly, neurological dysfunction, coagulopathy, liver dysfunction, cytopenias, hypertriglyceridemia, hyperferritinemia, hemophagocytosis, and reduced natural killer cell activity [ 9 ]. Only two cases of HLH caused by C. jejuni have been reported thus far [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…HLH can present with a range of clinical and laboratory features, including fever, splenomegaly, neurological dysfunction, coagulopathy, liver dysfunction, cytopenias, hypertriglyceridemia, hyperferritinemia, hemophagocytosis, and reduced natural killer cell activity [ 9 ]. Only two cases of HLH caused by C. jejuni have been reported thus far [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 9) Only two cases of HLH caused by C. jejuni have been reported thus far. (10,11) To our knowledge, there have been no reported cases of Campylobacter causing both HLH and perimyocarditis. After ruling out other possible diagnoses, we concluded that Campylobacter infection triggered an autoimmune response, resulting in the development of both HLH and perimyocarditis in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the GBS patients have IgG antiganglioside antibodies, ,,, and in many patients with AMAN and AMSAN, they are directed against GM1 and GD1a, but they can also be directed against other gangliosides. ,,, Up to 90% of the patients with MFS have antibodies against the GQ1b ganglioside, but antibodies against other gangliosides were also identified. ,,, Cell culture studies and animal models of AMAN found that anti-GM1 antibodies block voltage-gated Na + channels, which are important for neuronal excitability and function, at the nodes of Ranvier by initiating a complement-mediated attack. , …”
Section: Molecular Mimicrymentioning
confidence: 99%